Prosumsi Sebagai Komodifikasi Pada Platform Media Online - Rara Mustika Ningrum (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This article discusses the phenomenon of prosumption and commodification in the context of online media platforms. By leveraging digital technology and the internet, online media not only transforms the patterns of information consumption but also involves audiences in the content production process. This phenomenon creates a new form of capitalism, known as prosumer capitalism, where the boundaries between producers and consumers become blurred. Online media exploits user-generated content without providing adequate compensation, turning it into a commodity that supports media operations. The commodification process involves content, audiences, and workers through various strategies, including clickbait, social media integration, and community-based marketing. This article highlights the social, economic, and exploitative impacts of these practices while emphasizing the potential for further transformation with the advancement of digital technology.